Assessment of TRAIN’s Coal and Petroleum Excise Taxes: Environmental Benefits and Impacts on Sectoral Employment and Household Welfare - Tuaño, Philip Arnold P. (Archīum Ateneo, 2021)
This study assessed the impact of the first package of the Tax Reform for Acceleration and Inclusion (or TRAIN) Law, which includes an increase in petroleum and coal excise taxes, as passed by Congress in 2017. This study reviewed the context of the energy sector in the country given that petroleum and coal are the largest sources of energy in the country. Using a computable general equilibrium-microsimulation model, it mainly assessed the impact of this increase and of the whole TRAIN 1 package (which includes a reduction in the personal income tax and the broadening of the value added tax). The results from the simulations show that there is a slight adverse output effect for most industries under an increase in petroleum and coal taxes scenario, resulting in a lower level of carbon emissions. There is a slight decline in employment, and poverty incidence increased slightly as excise taxes have an adverse effect in terms of higher commodities prices among the poor.